The impact of right ventricular energy failure on the results of pulmonary endarterectomy and balloon pulmonary angioplasty in patients with chronic thromboembolic pulmonary hypertension - MUTLU, BÜLENT; YILDIZELİ, BEDRETTİN; ATAŞ, HALİL (My University, 2024)
Objective: We aimed to investigate the effect of right ventricular energy failure (RVEF) on hemodynamic and clinical outcomes in patients diagnosed with chronic thromboembolic pulmonary hypertension (CTEPH) undergoing pulmonary endarterectomy (PEA) surgery or balloon pulmonary angioplasty (BPA). Patients and Methods: A total of 100 CTEPH patients planned for PEA or BPA were included in the study. Based on the presence of RVEF during diagnosis, patients divided into two groups. Hemodynamic data from right heart catheterization (RHC) were compared before and after procedures in 3-6 months follow up period. Results: Patients with RVEF revealed a decrease in mean pulmonary artery pressure (mPAP) from 54.67±12.27 mmHg to 36.12±11.76 mmHg (p:<0.001), mean right atrial pressure (mRAP) from 13.40±4.08 mmHg to 9.76±4.56 mmHg (p:0.003), and pulmonary vascular resistance (PVR) from 11.36±5.15 Wood Units (WU) to 5.46±3.30 WU (p <0.001). In the non-RVEF group, mPAP decreased from 38.82±12.61 mmHg to 30.81±10.57 mmHg (p:<0.001), mRAP from 7.09±3.02mmHg to 7.15±3.07mmHg (p: 0.917), and PVR from 6.33±3.65 WU to 4.09±2.31 WU (p:<0.001). Conclusion:The presence of RVEF at the time of diagnosis in CTEPH patients does not have a negative impact on early perioperative and 3-month postoperative outcomes following PEA or BPA. This high-risk patient group demonstrated significant hemodynamic and clinical benefits from both PEA and BPA.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Chronic thromboembolic pulmonary hypertension; Pulmonary balloon angioplasty; Pulmonary endarterectomy; Right ventricular energy failure